Pemberdayaan Remaja Pra Sejahtera dalam Peningkatan Kesehatan Ibu dan Anak - Mirta, Surya Bin; Yuliani, Ita; Yulindawati, Asworoningrum; Dumilah, Retno (FORIKES, 2025)
Pre-prosperous adolescents are often burdened by family caregiving and economic responsibilities, which can hinder access to education and welfare. The purpose of this study was to determine the effectiveness of empowering pre-prosperous adolescents in improving maternal and child health. This study is a systematic literature review, sourced from Google Scholar, published between 2020 and 2024. The systematic flow used was Preferred Reporting Items for Systematic Reviews and Meta-Analyses, resulting in the selection of six eligible articles. The results of the six articles demonstrate the success of education- and economic-based programs, which combine digital technology, peer educator training, and economic empowerment through skills and entrepreneurship, effectively increasing adolescent access to reproductive health information and services. Cross-sectoral policy integration involving the government, private sector, and communities can strengthen the positive impact on maternal and child health. It is concluded that adolescent empowerment must be carried out holistically and multi-sectorally to create a healthy and independent generation.Keywords: adolescents; empowerment; maternal-child health; education; economy; multi-sector ABSTRAK Remaja pra sejahtera sering terbebani oleh tanggung jawab pengasuhan dan ekonomi keluarga, yang bisa menghambat akses terhadap pendidikan dan kesejahteraan. Tujuan dari studi ini adalah mengetahui keberhasilan pemberdayaan remaja pra sejahtera dalam peningkatan kesehatan ibu dan anak. Studi ini merupakan systematic literature review, bersumber dari Google Scholar, yang dipublikasikan pada tahun 2020 sampai 2024. Alur sistematis yang digunakan adalah Preferred Reporting Items for Systematic reviews and Meta-Analyses, sehingga terpilih 6 artikel yang layak. Hasil studi pada keenam artikel menunjukkan keberhasilan program berbasis edukasi dan ekonomi, yang menggabungkan teknologi digital, pelatihan peer educator, serta pemberdayaan ekonomi melalui keterampilan dan kewirausahaan, efektif meningkatkan akses remaja terhadap informasi dan layanan kesehatan reproduksi. Integrasi kebijakan lintas sektor yang melibatkan pemerintah, sektor swasta, dan komunitas dapat memperkuat dampak positif terhadap kesehatan ibu-anak. Disimpulkan bahwa pemberdayaan remaja harus dilakukan secara holistik dan multi sektor untuk menciptakan generasi yang sehat dan mandiri.Kata kunci: remaja; pemberdayaan; kesehatan ibu-anak; edukasi; ekonomi; multi sektor